A bi‐level model for co‐expansion planning of generation and energy storage system (ESS) with contract pricing. Issue 11 (2nd May 2021) - Rafiei, Seyed Arash; Rafiei, Seyed‐Raza; Goldani, Saeedreza; Falaghi, Hamid
Abstract: In co‐expansion planning of generation and storage systems, the investor aims to determine the time, location, and capacity of the generation energy storage units. The main challenge is to install these systems in a way that the investor's profit is maximized. In addition, market‐clearing must take place in order to optimize social welfare. This paper studies a co‐expansion planning problem as a bi‐level model that involves the expansion of generation and energy storage units. Generating units include wind and gas turbines and the energy storage system (ESS) is compressed air. This paper addresses the upper‐level problem of increasing investor profits and the lower‐level problem of increasing social welfare. Simulation results show that an investor can achieve the highest possible profit by simultaneously investing in the wind and gas turbine as well as the storage systems using strategic behaviour (price offer/bid close to market price) and participating in the spot market and guaranteed purchase contract. In addition, improving the load growth rate and guaranteed purchase contracts increase the investment in the generation‐storage units. The simulation results of this study are compared with other studies for validation purposes.